BARRIERS TO THE IMPLEMENTATION OF ARTICLE 43 SUB-SECTION (2) OF LAW NO.41 FROM 2004 REGARDING WAQF PROPERTY MANAGEMENT AND OPERATION OF THE PRODUCTIVE WAQF (Cash Waqf Management Studies at Baitul Maal Hidayatullah Malang) - Talitha Rakhma Maulida (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThe emergence of a new discourse in exploring the potential of people who can be utilized to build communities solidarity through cash waqf concept. Cash waqfpractice is relatively new in Indonesia. This type represents waqf object other than land and building waqfs that are immovable. It strated with the introduction of waqf cash waqf certificate (cash waqf certificate) as well as the establishment of the Social Investment Bank Limited (SIBL)body, which function as an agency that raises funds from the wealthy people through cash waqf certificate. This study has the objective to be achieved at the end of this research, which is to describe and analyze the implementation of Article 43 paragraph (2) of Act 41 of2004 in the management and development of waqf properties conducted productivally, to identify, describe, and analyze the distribution system of cash waqf funds received by the Baitul Maal Hidayatullah Malang providing benefits to the community, to identify, describe, and analyze the enabling and inhibiting factors experienced by Baitul Maal Hidayatullah Malang in receiving and managing cash waqf. This research is a juridical-empirical study on barriers for the implementation of Article 43 Paragraph (2) of Act 41 of 2004 on Waqf in the management and implementation of cash waqf property in a productive manner. The research approach used in this study is the juridical-sociological approach. It examines the problem in accordance with facts gathered fromthe field that could be linked to the prevailing legal norms, and the legal theories that exist. In effort to raise funds from the public in form of cash waqf, BMH Malang who directly or indirectly act as nadzir waqf, has taken several steps in the approachto potential benefactors in cash waqf program, through a religious approach and the social approach. Distribution of cash waqf funds that have been collected by BMH Malang put into a special fund group, because BMH realize that integrity of thesewaqf assets must be maintained. In promoting these cash waqf program,Â  BMH Malang realizes that there are some things that support as well as hinder BMH Malang measures.